2007
DOI: 10.1182/blood.v110.11.1720.1720
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Endothelial Cells Express Phosphatidylserine Receptor: A Functionally Active Receptor for Phosphatidylserine-Positive Erythrocytes.

Abstract: Phosphatidylserine (PS)-positive erythrocytes adhere to both endothelial cells and the sub-endothelial matrix components. While thrombospondin mediates these interactions, it is not known whether PS-associated erythrocyte-endothelial adhesion occurs in the absence of plasma ligands. Using ionophore-treated PS-expressing control erythrocytes, we demonstrate that PS-positive erythrocytes adhered directly to human lung micro-endothelial cells in the absence of plasma ligands, that this adhesion was further enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…RT‐PCR products of TF mRNA from THP‐1 cells (a positive control for TF induction) incubated in the absence (lane 5) or presence (lane 6) of 100 ng mL −1 lipopolysaccharide (LPS) are shown for comparison. β‐Actin mRNA, a constitutively expressing transcript, was coamplified with TF mRNA as an endogenous control for TF mRNA quantitation, using previously described primers [14]. The RT‐PCR products of TF mRNA (380 bp) and β‐actin mRNA (687 bp) from a representative gel are shown at the top.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT‐PCR products of TF mRNA from THP‐1 cells (a positive control for TF induction) incubated in the absence (lane 5) or presence (lane 6) of 100 ng mL −1 lipopolysaccharide (LPS) are shown for comparison. β‐Actin mRNA, a constitutively expressing transcript, was coamplified with TF mRNA as an endogenous control for TF mRNA quantitation, using previously described primers [14]. The RT‐PCR products of TF mRNA (380 bp) and β‐actin mRNA (687 bp) from a representative gel are shown at the top.…”
Section: Resultsmentioning
confidence: 99%
“…Cell surface TF expression was assessed using two complementary methods, including an enzyme‐linked immunosorbent assay (ELISA)‐based assay (intact cell monolayer) and flow cytometry (cell suspension), as previously described for endothelial adhesion receptors [14]. Total TF protein level was assessed by using western blotting of cellular proteins.…”
Section: Methodsmentioning
confidence: 99%
“…The exposure of PS is also the basis of MP generation . Setty et al demonstrated the existence of a specific phosphatidylserine receptor (PSR) being present on endothelial cells, thereby facilitating sickle red cell adhesion to the endothelium. Ongoing inflammatory processes are enhanced by sickling and may further contribute to expression of adhesion molecules; for example, tumour necrosis factor alpha (TNF‐α) and interleukin‐18 (IL‐18) can increase vascular cell adhesion molecule‐1 (VCAM‐1) on endothelial cells .…”
Section: Pathophysiology Of the Sickling Mechanismmentioning
confidence: 99%
“…In part, this phosphatidylserine exposure mediates binding and phagocytosis by macrophages. However, it also seems capable of inducing binding to endothelial cells with unknown consequences (Haynes et al, 2006;Setty & Betal, 2008). Microparticles displaying phosphatidylserine derived from erythrocytes (Allan et al, 1982), platelets (Wun et al, 1998) and endothelial cells (Shet et al, 2003) have been observed in sickle cell disease and thalassaemia (Westerman et al, 2008).…”
Section: Phosphatidylserine Exposurementioning
confidence: 99%